2018
DOI: 10.5539/gjhs.v10n7p69
|View full text |Cite
|
Sign up to set email alerts
|

Salvia Hispanica L (Chia Seeds) as Brain Superfood – How Seeds Increase Intelligence

Abstract: The influence of nutrition on cognitive abilities is undisputed in academic literature. Omega-3 fatty acids in particular delivered convincing results in several studies. In recent years chia seeds (Salvia Hispanica L) are becoming increasingly popular in Europe as well. In a trial the authors divided the study participants into two groups: an intervention group and a control group. The participants of the intervention group consumed a daily dose of 5 grams chia seeds over a time period of 21 days.In total, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, dietary ALA in chia seed did not modify plasma parameters of oxidative stress as well as the modification of antioxidative enzymes. The action of these antioxidative enzymes was not changed in the control (safflower group) compared to chia seed oil [29], [30].…”
Section: A Antioxidant Potentialmentioning
confidence: 85%
See 3 more Smart Citations
“…However, dietary ALA in chia seed did not modify plasma parameters of oxidative stress as well as the modification of antioxidative enzymes. The action of these antioxidative enzymes was not changed in the control (safflower group) compared to chia seed oil [29], [30].…”
Section: A Antioxidant Potentialmentioning
confidence: 85%
“…Rincón-Cervera et al [29] observed an increase in activity of carnitine palmitoyl-transferase I and an increase in deoxyribonucleic acid transcription factor peroxisome proliferator-activated receptor-α expression on a study involving rats. Chia-fed rats also showed an increased superoxide dismutase activity, carnitine acyl-carnitine transferase, glutathione peroxidase and increased glutathione monosulfide /glutathione disulfide (GSH/GSSG) ratio signifying an increase in the antioxidant status [2], [22], [29]. The lipogenic enzymes fatty acid synthase and acetyl-CoA carboxylase activity were also shown to be inhibited [2], [29].…”
Section: A Antioxidant Potentialmentioning
confidence: 96%
See 2 more Smart Citations
“…Various studies have revealed that one can measure the effects of polyunsaturated fats and other diets such as milk or oils. Onneken [28] conducted a study to look into how chia seeds increase intelligence. The research was based on the assessment of tests that evaluate cognitive performance.…”
Section: F Chia Seeds Oil and The Cognitive Abilitiesmentioning
confidence: 99%